2018
DOI: 10.1007/s00468-018-1777-x
|View full text |Cite
|
Sign up to set email alerts
|

Rooting big and deep rapidly: the ecological roots of pine species distribution in southern Europe

Abstract: Root properties can influence plant drought resistance, and consequently plant species distribution. Root structure strongly varies across biomes partly as a result of phylogeny. However, whether the spatial distribution of phylogenetically close plant species is linked to differences in root properties remains unclear. We examined whether root properties mediate the strong correlation between summer drought intensity and the spatial segregation of pine species native to southern Europe. For this, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
3
25
0
1
Order By: Relevance
“…thrives in mid-altitude Mediterranean areas characterised by hot and dry summers and less frequent frosts during the winter. Mediterranean P. pinaster grows roots faster and develops larger root systems than P. sylvestris, contributing to its greater capacity to colonise drier Mediterranean sites (Andivia et al, 2019). Indeed, forests dominated by P. sylvestris have suffered frequent episodes of droughtinduced dieback in its southernmost peripheral population (Galiano et al, 2010), whereas Mediterranean P. pinaster forests at the southern distribution limit have demonstrated a high plasticity in their growth responses to drought (Caminero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…thrives in mid-altitude Mediterranean areas characterised by hot and dry summers and less frequent frosts during the winter. Mediterranean P. pinaster grows roots faster and develops larger root systems than P. sylvestris, contributing to its greater capacity to colonise drier Mediterranean sites (Andivia et al, 2019). Indeed, forests dominated by P. sylvestris have suffered frequent episodes of droughtinduced dieback in its southernmost peripheral population (Galiano et al, 2010), whereas Mediterranean P. pinaster forests at the southern distribution limit have demonstrated a high plasticity in their growth responses to drought (Caminero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that the root characteristics vary widely among plant species and these differences are due, in part, to adaptations to environmental conditions of plant habitats (ANDIVIA et al, 2019). On the other hand, species segregation along aridity and temperature gradients could be driven by differences in root architecture and growth (FRESCHET et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Pinus pinaster, P. halepensis) (Andivia et al 2019). This variability correlates with the species' ecological niches and the intensity of drought stress present in their environments (Andivia et al 2019). However, there is still a lack of information on the variability of functional root traits at the intraspeci c level, which determines the e ciency of water acquisition by trees (Kirfel et al 2017).…”
Section: Evidence For Intraspeci C Variability In Root Traits Of Alepmentioning
confidence: 99%
“…Indeed, there is strong evidence for genetic variability among populations originating from distinct environments to tolerate water stress, which involves traits such as water-use e ciency (Voltas et al 2008), wood anatomy (Esteban et al 2010), biomass allocation (Chambel et al 2007), or use of water sources (Voltas et al 2015). Deeper and more developed root systems might also be related to the ability of Aleppo pine to cope with water de cit (Andivia et al 2019;Voltas et al 2015). As a result, root morphology may be a key characteristic to understand water use strategies and, consequently, drought resistance mechanisms in this species.…”
Section: Introductionmentioning
confidence: 99%